2022
DOI: 10.3390/medicina58101410
|View full text |Cite
|
Sign up to set email alerts
|

Additional Prognostic Value of Tissue Doppler Evaluation in Patients with Aortic Stenosis and Left-Ventricular Systolic Dysfunction Undergoing Aortic Valve Replacement

Abstract: Background and Objectives: Patients with surgical aortic stenosis (AS) show impaired diastolic filling, which is a risk factor for early and late mortality after aortic valve replacement (AVR). There is a paucity of information concerning the impact of restrictive diastolic filling and the evolution of diastolic dysfunction in the early and medium terms post-AVR. We aimed to determine the prognostic value of the presence of a restrictive left-ventricular (LV) diastolic filling pattern (LVDFP) and dilated left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
2
10
1
Order By: Relevance
“…On the other hand, data from the present study are in line with the results from other studies demonstrating that LV diastolic filling is an important predictor of severity and prognosis in DCM [22,23]. The restrictive LVDFP is frequently observed in DCM, especially in most severe forms of the disease, and is the best predictor for cardiac death [24][25][26][27]. Thus, in our study, the mortality rate at 2-year follow-up was significantly higher in patients with DCM with restrictive LVDFP compared with those with a nonrestrictive filling pattern.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, data from the present study are in line with the results from other studies demonstrating that LV diastolic filling is an important predictor of severity and prognosis in DCM [22,23]. The restrictive LVDFP is frequently observed in DCM, especially in most severe forms of the disease, and is the best predictor for cardiac death [24][25][26][27]. Thus, in our study, the mortality rate at 2-year follow-up was significantly higher in patients with DCM with restrictive LVDFP compared with those with a nonrestrictive filling pattern.…”
Section: Discussionsupporting
confidence: 92%
“…The survival rate was 84%, 73% and 61% at 1, 2 and 4 years respectively in another study dealing with DCM patients, that is significantly lower compared to that of age-and gender-matched population. [26]. At the 2-years follow-up, in the group with standard treatment, we found a mortality rate slightly higher than those from the literature, probably because of the transplantation surgery which is not well developed in our country, and also because of the underuse of novel treatments, such as sacubitril.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the presence of a restrictive diastolic pattern determined a more unfavorable postoperative evolution both in patients with AS and in patients with AR. Severe diastolic dysfunction was identified by regression analysis as an independent risk factor for death and hospitalization for heart failure, as other studies have shown [ 1 , 5 , 10 , 28 ] [ 30 , 31 ]. Therefore, we also sought to assess whether preoperative restrictive diastolic filling precluded postoperative LV remodeling and improved function, and thus might prove useful in identifying patients who benefit less from AVR.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, restrictive filling is strongly predictive of mortality, especially if it is not reversible after treatment [ 27 , 32 ]. Diastolic dysfunction proved to be a more important predictor of mortality and unfavorable postoperative evolution compared to LV dilation and severe systolic dysfunction both in patients with AS and in those with AR [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intra aortic balloon pump (IABP) effectively supports declining circulation in subjects at high risk of post-operative cardiovascular events. Research has also shown its survival benefits in subjects with low ejection fraction (Escutia-Cuevas et al, 2020;Heuts et al, 2023;Iliuta et al, 2022). However, IABP use is associated with complications like infection, paraplegia, stroke, hemolysis, aortic or iliac dissection bleeding, and limb ischemia; moreover, it's intensive care treatment and is costly He and Gao, 2019).…”
Section: Introductionmentioning
confidence: 99%